The research of methods for decreasing ingress of dust into atmospheric air during bulk material sintering - Shishackiy, A. G.; Picyk, J. V. (Science and Transport Progress, 2012)
The analysis of aggloburden balling process and procedure of bulk materials adhesion was performed in this article. The laboratory bench for definition of adhesive force of bulk material breaking was developed and the research of suspended materials concentration of sintering gas throwing into atmospheric air during aggloburden sintering was performed. The decreasing of dust concentration as a result of aggloburden treatment with solutions of surfactant species was disclosed and its optimal consumption was determined.